Al-Ālaqah baina Tafsīr Āyāt al-Aḥkām wa al-Fiqh al-Muqāran al-Nasy’ah wa al-Taţawwur - Elhut, Mücahit (Study Program of Arabic Language Teaching, 2025)
The Holy Qur’an, being the primary source of legislation in Islamic jurisprudence, has motivated Muslim scholars to dedicate efforts to its study, understanding, and application. Among these scholars are jurists who not only engaged in jurisprudence but also endeavored to systematize the Qur'anic verses containing legal rulings in a unique organizational framework, distinct from traditional jurisprudential writing. Some scholars combined opinions from various schools of thought, employing a comparative jurisprudence approach. This approach is clearly embodied in the works of Al-Qurtubi, who, although he provided a complete exegesis of the Qur'an, distinguished his work by its jurisprudential nature, incorporating the views of scholars from multiple schools of thought. Some scholars focused on a single school, though occasionally referencing others, such as Al-Jassas, who supported his views with evidence. Other works were based on the Shafi’i school, such as